Implementasi E-Filling System sebagai Pusat Penyimpanan Data Perusahaan Medi Groups berbasis Cloud dengan menggunakan Aplikasi Google One - Astawan, I Kadek Todi (Jurnal Manajemen Sistem Informasi (JMASIF), 2022)
Digital based data management & storage becomes a vital infrastructure that are needed by the most of companies, nowadays. It is dominantly influenced by the massive development of digital technology that enables us to manage and store the data in form of digital files. Medi Groups is a holding company that provides some services in development and placement of Tourism Labors. The aim of this study is to describe the implementation of Google One Platform as an integrated cloud-based data management and storage. This study is a descriptive study with qualitative approach. There are 3 techniques of data collection applied such as observation, documentation, and interview toward 5 Corporate Officers and 4 Unit Managers. The result of this study showed that the implementation of E-Filling System became an innovation and solution for data management and storage which were more effective, safe, and user friendly. Besides that the system can improve the company efficiency because mostly the data were managed and stored with paperless system.